Emphysematous pyelonephritis with Dengue hemorrhagic fever: A successful medical management of a fatal scenario - Manappallil, Robin George; Muthyala, Prathap Reddy (Asian Journal of Medical Sciences, 2017)
Emphysematous pyelonephritis is a life threatening acute necrotizing infection with associated gas formation involving the renal parenchyma and perinephric tissues. Dengue fever, according to the WHO, is the most rapidly spreading mosquito borne viral infection in the world. Dengue Hemorrgahic Fever is a more severe form of dengue fever and is characterized by fever, bleeding manifestations, plasma leakage and thrombocytopenia. This is a case of a 56 year old female, who presented with history of fever, headache, myalgia and dysuria; and was diagnosed to have emphysematous pyelonephritis with Dengue Hemorrgahic Fever. She was successfully managed with intravenous antibiotics and platelet transfusions, without any urological interventions. Asian Journal of Medical Sciences Vol.8(5) 2017 101-103